Small Bowel Dissemination of Coccidioidomycosis - Shengmei Zhou; Yanling Ma; Parakrama Chandrasoma (Hindawi Limited, 2015)
Gastrointestinal coccidioidomycosis is extremely rare, with less than 10 cases reported in the literature. We report a case of small bowel dissemination of coccidioidomycosis in a 21-year-old African American male with a history of living in San Joaquin Valley. The patient presented with one week of abdominal pain, nausea, shortness of breath, intermittent fever, and sweat, and one month of abdominal distention. A chest radiograph revealed complete effusion of left lung. A computed tomography scan of the abdomen showed diffuse small bowel thickening and enhancement, as well as omental and peritoneal nodules, and ascites. The coccidioidal complement fixation titer was 1 : 256. The duodenal biopsy revealed many spherules filled with round fungal endospores. Later, blood fungal culture showed positivity for Coccidioides immitis. The final diagnosis is disseminated coccidioidomycosis involving lungs, blood, and duodenum. Despite aggressive antifungal therapy, the patient's clinical situation deteriorated and he succumbed to multisystem organ failure one and half months later. A high index of suspicion for gastrointestinal coccidioidomycosis should be maintained in patients from an endemic area presenting as abdominal distention and pain.